Using High-Resolution Bus GPS Data to Visualize and Identify Congestion Hot Spots in Urban Arterials. Issue 1 (2016) - Stoll, Nicholas B.; Glick, Travis; Figliozzi, Miguel A.
Congestion and travel delay on urban roadways can influence the roadways' operating costs and service attractiveness. This research used high-resolution bus data to examine sources of delay on urban arterials. A set of tools was created to help visualize trends in bus behavior and movement; these tools allowed larger traffic trends to be visualized along urban corridors and streets. With buses as probes and examining aggregated bus behavior, contoured speed plots were used to understand the behavior of roadways outside the zone of influence of bus stops. Speed plots were used to discover trends and travel patterns with only a few days' data. Congestion and speed variation were viewed by time of day, and plots helped to indicate delays caused by intersections, crosswalks, or bus stops. This type of information is important to transit authorities looking to improve bus running times and reliability. Congested areas were detected and ranked. Speed plots were used to reevaluate bus stop locations (e.g., near side versus far side) and to identify locations where improvement are needed (e.g., queue jump lanes). Transportation agencies can also benefit from this type of information because arterial performance measures are difficult to estimate.